LIPIDS OF BLACK SEA ALGAE: UNVEILING THEIR POTENTIAL FOR PHARMACEUTICAL AND COSMETIC APPLICATIONS - Veselina Panayotova; Albena Merzdhanova; Diana A. Dobreva; Magdalen Zlatanov; Lubomir Makedonski (Peytchinski Publishing, 2017)
Background: Bulgarian Black Sea coast is rich in algae, regarding biomass and algal biodiversity. The red algae Gelidium crinale (Rhodophyta) and brown algae Cystoseira barbata (Phaeophytes) are among the most abundant species along the Bulgarian Black Sea shore. Yet information about their lipid composition is limited. Purpose: Present study was conducted to investigate biologically active substances in two underexplored seaweed lipids. Total lipids, total phospholipids, fat soluble vitamins and carotenoids were analysed. In addition, the specific distribution of fatty acids group among the total lipids and total phospholipids were elucidated. Material/Methods: The saponifiable lipid fraction was derivatized into fatty acid methyl esters (FAMEs) and analysed by gas chromatography-mass spectrometry (GC-MS) to identify and quantify the fatty acids. The fat soluble non-saponifiable lipids were identified by high-pressure liquid chromatography coupled with UV/Vis and fluorescence detectors (HPLC-UV-FL). Results: Results showed that Rhodophyta and Phaeophytes have high concentrations of polyunsaturated fatty acids (PUFA), particularly from the n-3 series, thereby being a good source of these compounds. They presented a "healthy" n-6/n-3 ratio. Both seaweed species showed considerably high amounts of α-tocopherol, β-carotene and astaxanthin. Conclusions: The study reveals that lipids from Black Sea algae have a high potential as natural sources of biologically active ingredients. They are balanced source of fatty acids and contained beneficial antioxidants, such as α-tocopherol, β-carotene and astaxanthin.